2018
DOI: 10.1111/his.13427
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of prostate cancer patients with overall biopsy Gleason score 3 + 4 = 7 and highest Gleason score 3 + 4 = 7 or > 3 + 4 = 7

Abstract: Among patients with overall GS 3 + 4 = 7, those with highest GS > 3 + 4 = 7 had worse clinicopathological features, but clinical outcome was not statistically significant. Therefore, the use of overall GS instead of highest GS for clinical decision-making is justified, potentially preventing overtreatment in prostate cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Some consider patients with GG2 prostate cancer amenable for active surveillance dependent upon the proportion of Gleason pattern 4 carcinoma, [21][22][23] but more recent studies suggested that the presence of IDC/CC would represent a stronger contraindication for deferred treatment than percentage-high (Gleason grade 4) prostate cancer. 7,24 The high positive predictive value of IDC/ CC at biopsy (90%) and its strong association with advanced pathological stage would support this notion. Conversely, NPV at biopsy for IDC/CC was moderate (60%), and therefore its absence in the biopsy cannot serve as a sufficiently reliable stand-alone biomarker for deferred treatment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some consider patients with GG2 prostate cancer amenable for active surveillance dependent upon the proportion of Gleason pattern 4 carcinoma, [21][22][23] but more recent studies suggested that the presence of IDC/CC would represent a stronger contraindication for deferred treatment than percentage-high (Gleason grade 4) prostate cancer. 7,24 The high positive predictive value of IDC/ CC at biopsy (90%) and its strong association with advanced pathological stage would support this notion. Conversely, NPV at biopsy for IDC/CC was moderate (60%), and therefore its absence in the biopsy cannot serve as a sufficiently reliable stand-alone biomarker for deferred treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Our results are of potential relevance for the selection of men who could defer active treatment. Some consider patients with GG2 prostate cancer amenable for active surveillance dependent upon the proportion of Gleason pattern 4 carcinoma, but more recent studies suggested that the presence of IDC/CC would represent a stronger contraindication for deferred treatment than percentage‐high (Gleason grade 4) prostate cancer . The high positive predictive value of IDC/CC at biopsy (90%) and its strong association with advanced pathological stage would support this notion.…”
Section: Discussionmentioning
confidence: 99%
“…a highest score exceeding the global score. 44 The outcome of those men did not differ significantly from men in which the highest Gleason score was 3 þ 4 ¼ 7. The authors recommended the use of global Gleason score in order to avoid overtreatment.…”
Section: Reporting Of Grades On Needle Biopsies: Global Vs Highest Gmentioning
confidence: 86%
“…In a review of 370 biopsies with a global Gleason score of 3 + 4 = 7 from the European Randomised Study of Screening for Prostate Cancer (ERSPC), 16% of cases had individual cores with a Gleason score of 4 + 3 = 7 or 4 + 4 = 8, i.e. a highest score exceeding the global score . The outcome of those men did not differ significantly from men in which the highest Gleason score was 3 + 4 = 7.…”
Section: Current Controversiesmentioning
confidence: 99%
“…In a recent issue, Verhoef et al analysed European Randomized Study of Screening for Prostate Cancer (ERSPC) data in patients with global GS 3 + 4 = 7 to compare clinical outcomes of patients with worst GS 3 + 4 with those with worst GS > 3 + 4. 8 Unlike previous studies comparing the utility of global GS and worst GS to predict outcome in needle biopsies, these authors have focused specifically on cases with global GS 3 + 4 = 7 in which the worst GS was different (almost always higher) from the global GS. Their findings confirm that there is no statistically significant difference in clinical outcome using either global GS or worst GS.…”
mentioning
confidence: 99%